PROFESSIONAL POSITION OF HER ROLE IN INTERACTION TEACHERS AND STUDENTS IN LESSON (Pedagogy of Higher and Secondary Education, 2006)
The author of the article highlights the influence of active professional position on the psychological climate of lesson.